2020
DOI: 10.1007/s00431-019-03563-w
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination during pregnancy: current and possible future recommendations

Abstract: Immunizing pregnant women to protect the mother, fetus and infant from infection has increasingly been used over the last decade. Protection against infectious diseases in neonates is mainly provided by maternal antibodies transferred from mother to infant during pregnancy through transplacental transport or after delivery via breastfeeding. Both the transplacental-and breast milk-derived maternal antibodies function as the primary source of protection against infectious diseases in neonates during the first v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 65 publications
(51 reference statements)
0
40
0
1
Order By: Relevance
“…The concept of maternal vaccination is in fact quite well-accepted in the field of infectious diseases. Maternal vaccination is considered particularly in the field of influenza ( 104 , 105 ), group B streptococcus diseases ( 106 ), pertussis ( 107 ), and several other infectious diseases as safe and effective ( 108 110 ).…”
Section: Unique Features Of Recombinant B Cell Epitope-based Peptide mentioning
confidence: 99%
“…The concept of maternal vaccination is in fact quite well-accepted in the field of infectious diseases. Maternal vaccination is considered particularly in the field of influenza ( 104 , 105 ), group B streptococcus diseases ( 106 ), pertussis ( 107 ), and several other infectious diseases as safe and effective ( 108 110 ).…”
Section: Unique Features Of Recombinant B Cell Epitope-based Peptide mentioning
confidence: 99%
“…Maternal vaccination has the potential to protect pregnant women and their infants by enabling the transfer of antibodies from mother to child via the placenta and in breastmilk [4]. Currently, the WHO recommends maternal vaccination against tetanus, pertussis, and influenza, as well as other vaccines such as pneumococcus [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most effective strategy to prevent severe pertussis in young infants is maternal immunization in the second or third trimester of each pregnancy. Many studies have shown that tetanus-diphtheria-acellular pertussis (Tdap) vaccination is safe for both mother and child and highly effective in preventing severe and deadly pertussis in the new-born (for a recent review, see [ 30 ]). Protection in the new-born is due to the active transplacental transport of the maternal aP-induced antibodies to the fetus.…”
Section: Effect Of Pertussis Vaccination and The Recent Resurgencementioning
confidence: 99%
“…Barriers to pregnancy vaccination include the perception of low prevalence and severity of the disease, lack of information about vaccine recommendations, concerns about safety for mother and child, as well as economic status and educational levels [ 31 ]. Furthermore, studies have shown that maternal antibodies may interfere with the immune responses to wP in the infants [ 33 , 34 ], although less so with the responses to aP [ 30 ]. However, since today most children in the world receive wP for their primary immunization series, the clinical consequences of blunting by maternal aP-induced antibodies need to be carefully evaluated.…”
Section: Effect Of Pertussis Vaccination and The Recent Resurgencementioning
confidence: 99%